In-process truing for ELID (Electrolytic In-Process Dressing) grinding by pulsewidth control - Saleh, Tanveer; Rahman, Mustafizur (IEEE, 2011)
Electrolytic in-process dressing (ELID) grinding is a well established technology for achieving highest quality surface finish on hard and brittle materials such as optical glass, ceramics, and silicon compounds. In conventional ELID grinding, constant voltage is applied on the metal-bonded diamond wheels to ensure constant protrusion of super fine cutting grits throughout the grinding cycle. However, this method is not suitable to achieve grinding wheel truing which is very important to maintain the stability of the grinding. In this study, a novel approach of wheel truing has been developed by controlling the dressing voltage duty ratio for ELID grinding. An inductive sensor is used to measure the wheel profile based on the gap between the sensor head and wheel edge, and this is used as the feedback signal to control the duty ratio of the power supply. Detailed mathematical design of the control algorithm has been presented and simulation results have been substantiated by experimental findings. The experimental finding shows that the wheel work piece contact gradually improves from 40° to ~ 360° as the grinding progresses when this new controlled dressing technique is implemented.